The effect of Posner's model on learning the skills of handling and suppression in football (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the research is to prepare educational units using the Posner model in learning the skills of handling and suppressing football, implementing them, and identifying them. The researcher used the experimental approach for its suitability with the nature of the problem and the objectives of the research, "as the experimental approach is considered one of the best scientific research methods for solving problems. The research selected 20 students from grade A to represent the control group and 20 students from grade B to represent the experimental group.One of the most important conclusions of the research is that the use of Posner's model encouraged students to contribute to creativity and self-correct information in proportion to their experiences, skills and personal talents.Posner's model has a positive effect In the learning units using various motor exercises and learning the skills of handling and suppression with football, and through the results of all skill tests, the students' learning levels improved better and their cognitive capabilities of the skills under study increased. And stay away from the traditional ways that bring boredomKeywords: Posner's model: learning: skills: football: motor exercises.